Correlating MRI-based brain volumetry and cognitive assessment in people with Down syndrome - Hamadelseed, Osama; Skutella, Thomas (Brain and behavior, 2023)
Introduction Down syndrome (DS) is the most common genetic cause of intellectual disability. Children and adults with DS show deficits in language performance and explicit memory. Here, we used magnetic resonance imaging (MRI) on children and adults with DS to characterize changes in the volume of specific brain structures involved in memory and language and their relationship to features of cognitive-behavioral phenotypes. Methods Thirteen children and adults with the DS phenotype and 12 age- and gender-matched healthy controls (age range 4-25) underwent an assessment by MRI and a psychological evaluation for language and cognitive abilities. Results The cognitive profile of people with DS showed deficits in different cognition and language domains correlating with reduced volumes of specific regional and subregional brain structures, confirming previous related studies. Interestingly, in our study, people with DS also showed more significant parahippocampal gyrus volumes, in agreement with the results found in earlier reports. Conclusions The memory functions and language skills affected in studied individuals with DS correlate significantly with the reduced volume of specific brain regions, allowing us to understand DS's cognitive-behavioral phenotype. Our results provide an essential basis for early intervention and the design of rehabilitation management protocols.
Gesehen am 31.07.2023